Prejunctional muscarinic inhibitory control of acetylcholine release in the human isolated detrusor: involvement of the M(4) receptor subtype - D'Agostino, Gianluigi (2000)
1. Experiments were carried out in human detrusor strips to characterize muscarinic receptor subtypes involved in the prejunctional regulation of acetylcholine (ACh) release from cholinergic nerve terminals, and in the postjunctional smooth muscle contractile response. 2. In detrusor strips preincubated with [(3)H]-choline, electrical field stimulation (600 pulses) delivered in six trains at 10 Hz produced a tritium outflow and a contractile response. In the presence of 10 μM paraoxon (to prevent ACh degradation) the tritium outflow was characterized by HPLC analysis as [(3)H]-ACh (76%) and [(3)H]-choline (24%). 3. Electrically-evoked [(3)H]-ACh release was abolished by tetrodotoxin (TTX: 300 nM) and unaffected by hexamethonium (10 μM), indicating a postganglionic event. It was reduced by physostigmine (100 nM) and the muscarinic receptor agonist, muscarone (10 nM–1 μM), and enhanced by atropine (0.1–100 nM). These findings indicate the presence of a muscarinic negative feedback mechanism controlling ACh release. 4. The effects of various subtype-preferring muscarinic receptor antagonists were evaluated on [(3)H]-ACh release and muscle contraction. The rank potency (−log EC(50)) orders at pre- and postjunctional level were: atropine ⩾4-diphenyl-acetoxy-N-piperidine (4-DAMP)>mamba toxin 3 (MT-3)>tripitramine>para-fluorohexahydrosiladiphenidol (pF-HHSiD)⩾methoctramine⩾pirenzepine>tripinamide, and atropine⩾4-DAMP>pF-HHSiD>>pirenzepine=tripitramine>tripinamide>methoctramine>>MT-3, respectively. 5. The comparison of pre- and post-junctional potencies and the relationship analysis with the affinity constants at human cloned muscarinic receptor subtypes indicates that the muscarinic autoreceptor inhibiting ACh release in human detrusor is an M(4) receptor, while the receptor involved in muscular contraction belongs to the M(3) subtype..